Strains in trussed spine interbody fusion implants are modulated by load and design. (April 2018) - Caffrey, Jason P.; Alonso, Eloy; Masuda, Koichi; Hunt, Jessee P.; Carmody, Cameron N.; Ganey, Timothy M.; Sah, Robert L.
Abstract: Titanium cages with 3-D printed trussed open-space architectures may provide an opportunity to deliver targeted mechanical behavior in spine interbody fusion devices. The ability to control mechanical strain, at levels known to stimulate an osteogenic response, to the fusion site could lead to development of optimized therapeutic implants that improve clinical outcomes. In this study, cages of varying design (1.00 mm or 0.75 mm diameter struts) were mechanically characterized and compared for multiple compressive load magnitudes in order to determine what impact certain design variables had on localized strain. Each cage was instrumented with small fiducial sphere markers (88 total) at each strut vertex of the truss structure, which comprised of 260 individual struts. Cages were subjected to a 50 N control, 1000 N, or 2000 N compressive load between contoured loading platens in a simulated vertebral fusion condition, during which the cages were imaged using high-resolution micro-CT. The cage was analyzed as a mechanical truss structure, with each strut defined as the connection of two vertex fiducials. The deformation and strain of each strut was determined from 50 N control to 1000 N or 2000 N load by tracking the change in distance between each fiducial marker. As in a truss system, the number of struts in tension (positive strain) and compression (negative strain) were roughly equal, with increased loads resulting in a widened distribution (SD) compared with that at 50 N tare load indicating increased strain magnitudes. Strain distribution increased from 1000 N (+156 ± 415 με) to 2000 N (+180 ± 605 με) in 1.00 mm cages, which was similar to 0.75 mm cages (+132 ± 622 με) at 1000 N load. Strain amplitudes increased 42%, from 346με at 1000 N to 492με at 2000 N, for 1.00 mm cages. At 1000 N, strain amplitude in 0.75 mm cages (481με) was higher by 39% than that in 1.00 mm cages. These amplitudes corresponded to the mechanobiological range of bone homeostasis+formation, with 63 ± 2% (p < .05 vs other groups), 72 ± 3%, and 73 ± 1% of struts within that range for 1.00 mm at 1000 N, 1.00 mm at 2000 N, and 0.75 mm at 1000 N, respectively. The effective compressive modulus for both cage designs was also dependent on strut diameter, with modulus decreasing from 12.1 ± 2.3 GPa (1.25 mm) to 9.2 ± 7.5 GPa (1.00 mm) and 3.8 ± 0.6 GPa (0.75 mm). This study extended past micro-scale mechanical characterization of trussed cages to compare the effects of design on cage mechanical behavior at moderate (1000 N) and strenuous (2000 N) load levels. The findings suggest that future cage designs may be modulated to target desired mechanical strain regimes at physiological loads. Graphical abstract: fx1 Highlights: Mechanical behavior of trussed spine cages with varying designs are compared. Thinner strut cages exhibit wider strain distribution with higher amplitudes. Strain amplitudes correspond largely to bone mechanobiological homeostasis. Effective modulus decreases non-linearly with strut diameter to values similar to that of normal trabecular bone.